The South African post office : on the brink - van der Hoven, Chris; Bowen, Amanda (London : Wits Business School, 2018)
Mark Barnes the CEO of state-owned South Africa Post office was three months behind his five plan to turn around the ailing fortunes of the post office and make the company financially self-sufficient. The case outlines the problems that the South African Post office faces and invites the student to consider what strategy there would implement to turn the company into a profitable business once more.
Originally Published Invan der Hoven, C., & Bowen, A. (2018). The South African Post Office: On the brink. WBS-2017-12. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Barnes, Mark; South Africa. -- Department of Posts and Telecommunications -- Case studies; Postal service -- South Africa -- Case studies; Postal service -- South Africa -- Finance -- Case studies